2010
DOI: 10.4238/vol9-3gmr825
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of transcription factors from the interaction between cacao and Moniliophthora perniciosa (Tricholomataceae)

Abstract: ABSTRACT. Cacao (Theobroma cacao) is one of the most important tropical crops; however, production is threatened by numerous pathogens, including the hemibiotrophic fungus Moniliophthora perniciosa, which causes witches' broom disease. To understand the mechanisms that lead to the development of this disease in cacao, we focused our attention on cacao transcription factors (TFs), which act as master regulators of cellular processes and are important for the finetuning of plant defense responses. We developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The same profile was observed during infection by Colletotrichum graminicola , and it was observed that the expression of the ZmbZIP65, 21 and 53 genes was increased after 96 h of infection [55]. Two cocoa bZIPs (RT42C09 and RT57A09) were studied according to their expression during Moniliophthora perniciosa infection, with expression increasing after the establishment of infection [56]. …”
Section: Bzips Responsive To Pathogens In Agronomic Cropsmentioning
confidence: 95%
“…The same profile was observed during infection by Colletotrichum graminicola , and it was observed that the expression of the ZmbZIP65, 21 and 53 genes was increased after 96 h of infection [55]. Two cocoa bZIPs (RT42C09 and RT57A09) were studied according to their expression during Moniliophthora perniciosa infection, with expression increasing after the establishment of infection [56]. …”
Section: Bzips Responsive To Pathogens In Agronomic Cropsmentioning
confidence: 95%
“…Terminal and axillary buds, flower cushions and developing pods are highly susceptible to witches’ broom infection, resulting in severe yield loss [27]. The genome of this pathogen was recently sequenced [28] and a deeper understanding of the mechanisms of pathogenicity is beginning to emerge [29-32]. In an effort to advance breeding of disease resistant varieties of cacao, we conducted research to further our understanding of the defense response in this tropical tree species.…”
Section: Introductionmentioning
confidence: 99%
“…The latter include studies focused mainly on the identification and characterization of genes (Chaidamsari et al 2006;Jones et al 2002). Such studies allowed to decipher expression and (putative) functions related for example pod color (Motamayor et al 2013), butter quality (Li et al 2019;Zhang et al 2015), flavonoid production (Gallego et al 2018;Liu et al 2013), drought stress (Bae et al 2008), soil flooding (Bertolde et al 2014), embryo maturation (Maximova et al 2014), sucrose transport (Li et al 2014), reference gene selection (Pinheiro et al 2011), cacao defense (Shi et al 2010(Shi et al , 2013Verica et al, 2004), and for understanding cacao diseases (Ali et al 2014(Ali et al , 2017Bailey et al 2006Bailey et al , 2013Bailey et al , 2014De Almeida et al 2017;Fister et al 2015Fister et al , 2016Gesteira et al 2007;Leal et al 2007;Legavre et al, 2015;Litholdo et al, 2015;Lopes et al 2010;Menezes et al 2014;Santana et al 2016).…”
Section: Introductionmentioning
confidence: 99%